School of Nursing, University of São Paulo: traces the history of the professionalization of nursing in Brazil - Thais Araujo da Silva taarsi2; Genival Fernandes de Freitas; Bárbara Barrionuevo Bonin; Elaine Corrêa da Silva; Fabíola de Campos Braga Mattozinho (Universidad de Alicante, 2017)
his paper aims to describe and analyze the contributions of the School of Nursing, University of São Paulo (EEUSP) in the construction and consolidation of professional nursing in Brazil, since its inception in the early 1940s. This is a socio-historical study on the legacy of the pioneering leaders of Brazilian nursing (Edith de Magalhães Fraenkel and Maria Rosa Sousa Pinheiro) and the examination of the latest contributions from other directors of EEUSP, with emphasis on the following themes: building of professional nursing, consolidation and strengthening of professional nursing education and nursing practices in Brazil. It sas outlined an itinerary of Brazilian nursing through the history of the professional life of Edith de Magalhães Fraenkel and Maria Rosa Sousa Pinheiro, first and second directors of EEUSP. The contributions of EEUSP for the professionalization of Brazilian nursing were numerous, especially in nursing education at the undergraduate and graduate levels and to strengthening of nursing as a socially and politically relevant practice in the national and international scenes through research and academic production.